The effect of flipped digital classroom method using moodle and student engagement on reading comprehension - Zelhendri Zen; Reflianto Reflianto; Farida Ariani; Abna Hidayati (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
English is a very urgent subject in academic life. In order to improve reading comprehension skills, teachers need to use online learning during the COVID-19 pandemic. This method is to provide space for students to study independently online. This study aimed to analyze the effect of the flipped digital classroom method using Moodle e-learning material and students’ engagement on students’ reading comprehension skills. This research used a quantitative approach with a quasi-experimental design. The instruments used in this research were observation sheets, questionnaires, and reading comprehension tests. The data analysis used Two Way ANOVA. The results showed that the flipped digital classroom method using Moodle and student engagement affect reading comprehension skills. English lecturers should apply this method by building a pleasant online learning atmosphere so that student engagement and reading comprehension skills increase.